ESTABLISHING WEATHER FORMAL COMMUNICATION CHANNEL SIGNIFICANTLY INFLUENCES EMPLOYEE’S PERFORMANCE AT IS IOLO COUNTY GOVERNMENT - Muriuki, Mukami Lydia, S.; Thruranira, Lydia (International Journal For Research In Business, Management And Accounting, 2021)
Employee’s performance is one of the core values of the vision 2030 of public service delivery in Kenyan Government. Communication channels are drivers of employee performance in any organization. Formal communication channels exist in the National and County Government organizations hence this study sought to investigate the influence of communication channels on enhancing employee performance at County Government of Isiolo. The study was guided by the objective: Formal communication channels and its influence on employee performance. The study was guided by three theories, which are Symbolic Interaction theory, Social Presence Theory and Structuration theory. Literature review was from primary and secondary data as presented by respondents and literature materials available to the researcher. For the research methodology, a descriptive study design was used in this study. The population target in this study included all the 1370 employees at County Government of Isiolo comprising of ten departments. Stratified random sampling was used to select 125 respondents. A structured questionnaire was used for data collection. Descriptive statistics such as frequencies, percentages was estimated for quantitative variables and the qualitative data from the openended questions was analyzed using conceptual content analysis, presented in prose, and displayed in tables. It was found that distortion; leakage of information and unreliable information greatly affected employee’s performance. The study concluded that formal communication channel had effect on employee performance at County Government of Isiolo. The study recommends that County Government of Isiolo should train staff on communication skills in order to enhance the performance of County employees on service delivery. The study also recommends that managers should make sure that appropriate communication channels are used in accordance to communication policy of the organization.